Short-Term Prognostic Efficacy of mGPS and LCS in Patients With Acute Heart Failure - Wang, Jing; Xie, Ling; Lyu, Ping; Zhou, Feng; Cai, Hong-Li; Qi, Rong-Xing; Zhang, Qing (Frontiers in Cardiovascular Medicine, 2022)
Aim Systemic inflammation plays an important role in the occurrence and development of acute heart failure. The modified Glasgow Prognostic Score (mGPS) and “lymphocyte C-reactive protein score” (LCS) are used to assess the inflammation levels in cancer patients. The purpose of this study was to assess the prognostic value of these two inflammation-related scoring systems in patients with acute heart failure. Methods Two hundred and fifty patients with acute heart failure were enrolled in this study. The mGPS and LCS scores were recorded after admission. All patients were divided into 2 groups: the death group and the survival group according to the 3-month follow-up results. The predictive values of mGPS and LCS were assessed using receiver-operating characteristic (ROC) analyses. Univariate and multivariate logistic analyses were used to evaluate the relationships between variables and endpoint. Results The levels of mGPS and LCS in the death group were significantly higher than those in the survival group (P < 0.05). The areas under the ROC curve of the mGPS and LCS for predicting death were 0.695 (95%CI: 0.567~0.823) and 0.736 (95%CI: 0.616~0.856), respectively. Multivariate analysis demonstrated that both LCS, LVEF and serum direct bilirubin were independent predictors of all-cause death, excluding mGPS. Conclusions Compared with mGPS, LCS is independently associated with short-term outcomes in patients with acute heart failure. LCS was a clinically promising and feasible prognostic scoring system for patients with acute heart failure.